Human Capital And Social Capital, And Their Influence On The Financial Performance Of Informal Agriculture-Based Industries - Charina, Anne (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
This study aims to investigate the impact of human capital and social capital on the performance of informal agriculture-based industries in West Java. This study also further investigates the role of Innovation as a controlling variable in the relationship between Social Capital and Human Capital on the Financial Performance of informal industries. The survey was conducted on 180 informal agriculture-based industry entrepreneurs in Sukabumi, Bogor and Bandung Regencies. Tests were conducted using the Partial Least Square model of the structural equation model (PLS SEM). The research findings revealed that social capital and social capital have a significant positive influence on the financial performance of agriculture-based informal industries. The results also show that the influence of social capital and human capital on financial performance will be better through innovations made by informal industries. Therefore, this study recommends that informal industry players utilize their human capital and social capital in a balanced manner in realizing better product, process and service innovations, so as to achieve sustainable financial performance.